On a subclass of Bazilevič functions - D. K. Thomas (International Journal of Mathematics and Mathematical Sciences, 1985)
Let B(α) be the class of normalised Bazilevič functions of type α>0 with respect to the starlike function g. Let B1(α) be the subclass of B(α) when g(z)≡z. Distortion theorems and coefficient estimates are obtained for functions belonging to B1(α).